How do Students Think in Translating Verbal Representation to Graphics? - Ummul Huda; Dona Afriyani; Mardiana Mardiana; Wiladahtul Fitri (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2021)
This research is based on the variety of students' work in completing mathematical translations, especially from verbal representations to graphs. This study aimed to analyze the path of students' mathematical translation thinking from verbal representations to graphs. Thirty-two students were involved in completing the mathematical translation task, and four students were selected as research subjects. The supporting instruments in this research are in the form of mathematical translation tasks and interview guidelines. The data analysis step begins by grouping the students' work and making a transcript of the interview results. Next, the researcher explored and coded the students' work, found differences in the mathematical translational thinking path, explained the mathematical translation process for each path, reported the findings, interpreted the findings, and validated the research results by triangulating data sources. This study resulted in two types of students' mathematical translational thinking paths, namely the complete and incomplete construction translational thinking path. The difference between these two paths lies in the completeness of cognitive activity in each step of mathematical translation. The results of this study are used as considerations in designing meaningful mathematics learning activities.